2008
DOI: 10.1111/j.1445-5994.2007.01595.x
|View full text |Cite
|
Sign up to set email alerts
|

End of life in the intensive care unit: knowledge and practice of clinicians from Karachi, Pakistan

Abstract: There are confusions in the definition of brain death, end-of-life recognition and indications and processes of withdrawal of life support. There are discrepancies between physicians' and nurses' perceptions and attitudes. Clearly, teaching programmes will need to incorporate cultural and religious differences in their ethics curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 17 publications
1
21
1
Order By: Relevance
“…A study of critical care nurses and physicians in Karachi in 2008 reported that 69% of the participants had adequate knowledge. 16 The knowledge level in our study did not tally with the respondents' attitude toward brain death. Surprisingly, 43.2% disagreed with the global consensus that brain death is equivalent to absolute clinical death.…”
Section: Discussioncontrasting
confidence: 64%
“…A study of critical care nurses and physicians in Karachi in 2008 reported that 69% of the participants had adequate knowledge. 16 The knowledge level in our study did not tally with the respondents' attitude toward brain death. Surprisingly, 43.2% disagreed with the global consensus that brain death is equivalent to absolute clinical death.…”
Section: Discussioncontrasting
confidence: 64%
“…Another study showed that uncertainties and discrepancies between physicians and nurses in terms of understanding were obvious in the process of the disconnection of the patient from the vital devices (35). It should be noted that most nursing systems have reached such uncertainties in different fields, although, such communities have been different in terms of religion and culture.…”
Section: Discussionmentioning
confidence: 99%
“…A study of over 600 Turkish intensive care nurses found that 40% of the respondents agreed with the statement that withholding or withdrawing medical care was considered unethical (Badir et al, ). In a study of Pakistani ICU physicians and nurses, 28% reported that they consider their medical duty to sustain life at all costs (Salahuddin et al, ).…”
Section: Introductionmentioning
confidence: 99%